Analysis of greedy perimeter stateless routing protocol network simulation using bird flocking algorithm - Doan Perdana; Albion Apta Zaim; Alfin Hikmaturokhman; Ananda Irsyad; Nindy Ayu Marthaliana (JURNAL INFOTEL, 2022)
The purpose of this study is to simulate the GPSR protocol network on NS3 using the bird flocking algorithm and to analyze the comparison of performance measurements obtained from the simulation results. The Greedy Perimeter Stateless Routing network was simulated using NS-3 in this simulation. The simulation area is created in length, width. The distance between nodes is 50 meters and is simulated in an area of 1000m x 300m for 30 seconds and 802.11 MAC protocol is used. This simulation was successfully implemented in finding the location of the nearest node using the GPSR protocol with the PSO / BFA algorithm. The number of nodes used in the simulation is 150 nodes and 2 nodes, so it can be concluded that the performance of Quality of Service (QoS) is greatly affected by the number of nodes and the algorithm used in the simulation.